Controle ativo de ruído em venezianas acústicas: um estudo teórico - experimental - Miranda, João Gabriel Oliveira de (2018)
The technological development of active noise control is advancing another step. This thesis comes to determine that the use of active noise control systems in acoustic vents also known for ventilated acoustic frames can be financially feasible and easily accessible. This thesis presents the simulated and experimental development of an acoustic vent with the hybrid implementation between active noise control system (active control, low frequencies) and acoustic foams (passive control, high frequencies) using the Arduino Due® as acquisition board for the controller. Active Noise Control (ANC) in ducts is a study in which the Laboratory of Acoustics and Vibrations of the Federal University of Uberlândia has been working for several years, and it is known that when applied to a wide frequency range, the system does not reach control satisfactorily. This thesis was developed aiming to reduce costs and also to understand the meaning of why some frequencies do not reach a satisfactory level of control. Through an experimental system of the ANC system using an acoustic vent and a signal generator, it was possible to obtain the FRF (Frequency Response Function) and from this analyze and verify which frequencies were acting in the anti-resonance regions (resulting a bad control) and which were acting in the resonant regions (resulting a good control). These evaluations made it possible to optimize the positioning of the actuators and achieve a greater number of discrete frequencies controlled satisfactorily in a single ANC project. This thesis concluded that the ANC system using Arduino Due® obtained significant responses reaching up to 30dB of attenuation in experimental bench.